2013
DOI: 10.1038/sj.bdj.2013.165
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss and osteoporosis: to assess the association between osteoporosis status and tooth number

Abstract: Clinicians should inform osteoporotic patients they may be at greater risk of tooth loss and instigate more intensive preventive regimens for these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 62 publications
1
43
2
4
Order By: Relevance
“…Darcy et al [19] & Passos et al [20] indicate the relationship between osteoporosis and tooth loss, which does not match with our studies. In Lundstram's [21] study also examined the relationship between osteoporosis and the number of missing teeth and the results showed no significant difference between osteoporosis and the number of missing teeth and results also match with the study.…”
Section: Discussioncontrasting
confidence: 97%
“…Darcy et al [19] & Passos et al [20] indicate the relationship between osteoporosis and tooth loss, which does not match with our studies. In Lundstram's [21] study also examined the relationship between osteoporosis and the number of missing teeth and the results showed no significant difference between osteoporosis and the number of missing teeth and results also match with the study.…”
Section: Discussioncontrasting
confidence: 97%
“…A previous study reported a significant relationship between a decreased number of remaining molar teeth and osteoporosis, and concluded that osteoporotic patients are more likely to lose teeth. 21 Our study failed to demonstrate a statistical correlation between tooth loss and decreased BMD.…”
Section: Discussioncontrasting
confidence: 70%
“…Forty-eight 3-month-old female Sprague-Dawley rats were randomly divided into two groups: an ovariectomized (OVX) group (n = 24) and Sham-operated (SHAM) group (n = 24). Six rats were randomly sacrificed from both groups at time points 8,12,16, and 20 weeks. The samples from tibia and maxilla were collected for micro computed tomography (mCT) and histological analysis.…”
mentioning
confidence: 99%